Anxiety Levels of Hypertensive Patients Against the Implementation of Covid-19 Vaccination in the Work Area of the Kawatuna Health Center - Hasnidar; Sukrang; Shasmy Tias Utami (Journal of Health and Nutrition Research, 2022)
This study aims to identify the level of anxiety of hypertensive patients regarding the implementation of the Covid-19 vaccination in the work area of the Kawatuna Public Health Center. The research design used was descriptive, with a total population survey design of 30 respondents. The study was conducted on 6 – 12 June 2022. The results of this study were the level of anxiety of hypertensive patients towards the implementation of the Covid-19 vaccination; most of the categories were moderate anxiety (46.6%), mild anxiety (13.3%), severe anxiety (30%), no anxiety (3.3%), and panic (6.6%). The study concluded that most hypertensive patients have moderate anxiety about implementing the Covid-19 vaccination, which was indicated by a positive attitude that controls anxiety. It is recommended that health workers improve their control of anxiety levels to be more effective such as teaching relaxation techniques, doing regular physical activity, and providing health counseling